Women's preferences for female-friendly public space design in Indonesia - Rusmana, Ajrina Rizkiananda; Abigail, Audrey (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
This study aims to analyse women's preferences for female-friendly public space design in Indonesia, focusing on comfort, safety, aesthetics, and facility needs. The research method employed a questionnaire-based survey involving 30 female respondents. The results indicate that women prioritise design elements such as comfortable seating, good air circulation, soft lighting, and accessible spaces. In terms of safety, the presence of security personnel, CCTV, and adequate sanitation facilities are considered essential. Preferred aesthetic elements include live plants, pastel or neutral colours, and simple, functional lighting. Additionally, respondents highly value specific facilities such as mother-and-child rooms, fire extinguishers, and first aid kits. The findings imply that public space designers and managers should consider these preferences to create inclusive and comfortable environments for women.